THE DEVELOPMENT OF PHYSICAL LITERACY RATING SCALE FOR THE UPPER SECONDARY SCIENCE GIFTED STUDENTS - Choptham, Titsana; Srisiri, Sununta; Wongyounoi, Somson; Moungsirithum, Pimpa (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2023)
The aims of this research are as follows: 1) to study the Physical Literacy factors for the upper secondary gifted science students; 2) to develop a Physical Literacy rating scale for upper secondary science gifted students. The Sample were 636 students from 11th grade students from Mahidol Wittayanusorn School and 6 Princess Chulabhorn Science High Schools. This research was conducted by: 1) study of the Physical Literacy factors for the upper secondary gifted science students by seven experts for interviewed with the EFR technique (Ethnographic Futures Research); 2) verified of Physical Literacy synthesis by five experts; and 3) develop a Physical Literacy and analysis of content validity, discrimination, reliability and construct validity by the sample. The tool for data collection was a semi-structured interview form, a Physical Literacy synthesis validation form and a Physical Literacy rating scale for the upper secondary gifted science students. The statistics for data analysis included Item Objective Congruence (IOC) used for content validity test, a t-test used for discrimination test, a Cronbach’s alpha coefficient used for reliability test, and confirmatory factor analysis used for construct validity test. The result showed that Physical Literacy rating scale consisted of four main factors, including the following: 1) knowledge; 2) physical skills and fitness; 3) mind, emotions and attitude; and 4) social skills with 108 questions. The quality of The Physical Literacy rating scale were in accordance with the specified criteria, including a content validity test (IOC index between 0.6-1.0), a discrimination test (t between 2.41 – 10.35), a reliability test (Cronbach’s alpha = 0.97), an overall construct validity test (Chi - square = 311.14, df = 167, p = 0.00, RMSEA = 0.04, GFI = 0.96, AGFI = 0.90, CFI=1.00, RMR=0.021, SRMR = 0.035).